Barriers and Facilitators to Implementing a Short-Term Transdiagnostic Mental Health Treatment for Homeless Persons. Issue 7 (July 2019) - Youn, Soo Jeong; Sauer-Zavala, Shannon; Patrick, Kaylie A.; Ahles, Emily M.; Aguilar Silvan, Yesenia; Greig, Astrea; Marques, Luana; Shtasel, Derri L.
Abstract : Abstract: Despite the significant mental health needs and comorbidity in homeless individuals, there is a "science-practice gap" between the available evidence-based treatments (EBTs) and their lack of use in community health centers servicing homeless populations. To address this gap, it is imperative to evaluate and attend to the contextual factors that influence the implementation process of EBTs before their integration into routine care. The study aims to evaluate the barriers and facilitators to implementing a transdiagnostic EBT in a community health center serving homeless individuals. The results of the thematic analyses (7 focus groups, 67 participants) yielded 8 themes for barriers and 10 themes for facilitators to implementation. The findings of the current study highlight common tensions faced by community programs and clinicians when working toward integrating EBTs across different types of populations, and those unique to homeless persons. Results can inform subsequent strategies used in implementing EBTs.